Alcohol dose in septal ablation for hypertrophic obstructive cardiomyopathy. (15th June 2021) - Veselka, Josef; Faber, Lothar; Liebregts, Max; Cooper, Robert; Januska, Jaroslav; Kashtanov, Maksim; Dabrowski, Maciej; Hansen, Peter Riis; Seggewiss, Hubert; Bonaventura, Jiri; Polakova, Eva; Hansvenclova, Eva; et al.
Abstract: Background: The aim of this study was to evaluate short- and long-term outcomes related to dose of alcohol administered during alcohol septal ablation (ASA) in patients with hypertrophic obstructive cardiomyopathy (HOCM). Current guidelines recommend using 1–3 mL of alcohol administered in the target septal perforator artery, but this recommendation is based more on practical experience of interventionalists rather than on systematic evidence. Methods: We included 1448 patients and used propensity score to match patients who received a low-dose (1.0–1.9 mL) versus a high-dose (2.0–3.8 mL) of alcohol during ASA. Results: The matched cohort analysis comprised 770 patients ( n  = 385 in both groups). There was a similar occurrence of 30-day post-procedural adverse events (13% vs. 12%; p  = 0.59), and similar all-cause mortality rates (0.8% vs. 0.5%; p  = 1) in the low-dose group and the high-dose group, respectively. In the long-term follow-up (5.4 ± 4.5 years), a total of 110 (14%) patients died representing 2.58 deaths and 2.64 deaths per 100 patient-years in the low dose and the high dose group (logrank, p  = 0.92), respectively. There were no significant differences in the long-term dyspnea and left ventricular outflow gradient between the two groups. Patients treated with a low-dose of alcohol underwent more subsequent septal reduction procedures (logrank, p  = 0.04). Conclusions: Matched HOCM patients undergoing ASA with a low-dose (1.0–1.9 mL) or a high-dose (2.0–3.8 mL) of alcohol had similar short- and long-term outcomes. A higher rate of repeated septal reduction procedures was observed in the group treated with a low-dose of alcohol. Highlights: ASA patients were treated either with low- or high dose of alcohol (1 – 1.9 mL vs 2 – 3.8 mL). Both groups had similar 30-day post-ASA mortality and occurrence of major adverse events. The matched patients had similar long-term mortality rates, dyspnoea and obstruction. The low-dose patients had a higher rate of repeated procedures.